Far-field thermal properties of β12 borophene under an external electric field. Issue 7 (3rd February 2023) - Xie, Wen-Wu; Qian, Wen-Ri; Zhang, Yong-Mei
Abstract : Radiation energy increases with temperature according to an approximately T 4 law. As voltage increases, the energy radiation decreases and deviates slightly from this law, revealing tunable emissivity by adjusting the electric field. Abstract : Borophene has been reported as the latest very promising 2D material. We theoretically investigate the thermal radiation of β12 borophene. β12 borophene has been composited on Ag substrate. Theoretical research frequently mentions three types of model of β12 borophene. The energy bands of the three models are different. Homogeneous and inversion symmetric models have a gapless Dirac cone near the K ( K ′) point, while they are gapped in the inversion non-symmetric model. The homogeneous model has gapless triplet fermions and three-band touching points at high-symmetry points. The optical conductivity exhibits peaks due to the energy transition of high-symmetry points. The radiation spectrum follows Wien's displacement law in homogeneous and inversion symmetric models, while it is broken in the inversion non-symmetric model. The total energy radiation changes as the voltage increases for the three β12 borophene models. The radiation of energy can be controlled by applying a suitable voltage.